PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS CONTEXTUAL LEARNING PADA MATERI SUMBER ENERGI DAN PERUBAHANNYA DI KELAS IV SD - Maulina Agustini; Lukman Nulhakim; Zerri Rahman Hakim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop a contextual learning-based audio visual media and its validity. This research utilized Research and Development (R&D) method, referring to Borg and Gall’s development model which consisted of 6 stages: (1) problems’ analysis, (2) data collection, (3) product design, (4) validation, (5) product revisions, and (6) product trials test. The study conducted to four grade students at SD Negeri Salatuhur. Based on the validity examined by the experts, media expert, language expert, and material expert, the average score of the validity from the media expert was 92% with a very feasible category. Then, the average score of the validity from the material expert was 85,49% with a very feasible category. At last, the average score of the validity from the language expert was 94,16% with also in the very feasible category. Moreover, the results of students’ responses obtained a score of 97,49% with a very feasible category. Based on the research results, the final product of a contextual learning-based audio visual media on material of the energy source and its change was feasible to utilized for students’ learning activities at four grade of elementary school.